A dual-application poly (DL-lactic-co-glycolic) acid (PLGA)-chitosan composite scaffold for potential use in bone tissue engineering - Boukari, Yamina; Qutachi, Omar; Morris, Andrew P.; Doughty, Stephen W.; Billa, Nashiru (Taylor & Francis, 2017)
The development of patient-friendly alternatives to bone-graft procedures is the driving force for new frontiers in bone tissue engineering. Poly (DL-lactic-co-glycolic acid), (PLGA) and chitosan are well-studied and easy-to-process polymers from which scaffolds can be fabricated. In this study, a novel dual-application scaffold system was formulated from porous PLGA and protein-loaded PLGA/chitosan microspheres. Physicochemical and in vitro protein release attributes were established. The therapeutic relevance, cytocompatibility with primary human mesenchymal stem cells (hMSCs) and osteogenic properties were tested. There was a significant reduction in burst release from the composite PLGA/chitosan microspheres compared with PLGA alone. Scaffolds sintered from porous microspheres at 37°C were significantly stronger than the PLGA control, with compressive strengths of 0.846 ± 0.272 MPa and 0.406 ± 0.265 MPa, respectively (p < 0.05). The formulation also sintered at 37°C following injection through a needle, demonstrating its injectable potential. The scaffolds demonstrated cytocompatibility, with increased cell numbers observed over an 8-day study period. Von Kossa and immunostaining of the hMSC-scaffolds confirmed their osteogenic potential with the ability to sinter at 37°C in situ.